Characterization of Postharvest Practices and Losses of Fresh Produce along the Caribbean Supply Chain: Guyana and St. Kitts-Nevis - Cortbaoui , Patrick E; Ngadi, Michael O (Journal of Postharvest Technology, 2016)
Inefficient handling and high postharvest losses describe the Caribbean supply  chain of fresh fruits and vegetables. In this study, two different approaches to characterize the postharvest practices and losses of key agricultural  commodities (tomato, string beans, eggplant, okra and cucumber) were  developed for Guyana and St. Kitts-Nevis: (1) producer household surveys  (PHS) and (2) modified count and weight (MCW). Results from the PHS  baseline surveys revealed that Caribbean farmers sell most of their harvested  crops to local markets, keeping the remaining crops for household  consumption. In Guyana, the majority of farmers (97%) reported selling their  crops at harvest, while in St. Kitts-Nevis, 61% of farmers stored their produces  before selling. One plausible explanation for this practice is that farmers delay  selling to obtain higher prices based on market demands. While farmers in St.  Kitts-Nevis reported 30% postharvest losses of crops due to spoilage, those in  Guyana reported considerably less. Results from modified count and weight  method revealed that small producers experienced greater postharvest loss  compared to large ones due to spoilage and lack of market access. A  reasonable explanation to this is the degree of knowledge in high-value crop  production between the two types of farmers. As the produce travelled  throughout the supply chain, it started to lose significantly (P < 0.05) its  freshness and its marketable value as well. At the marketing level, small and  large retailers in both countries experienced substantial postharvest  quantitative and qualitative losses. These losses were due to inappropriate  handling and exposure to undesirable environmental conditions.
Keywords: marketable; inappropriate; qualitative; undesirable; production